2024
DOI: 10.1590/1519-6984.252735
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic acclamatory response of Panicum antidotale Retz. populations to root zone desiccation stress

Abstract: Growth of plants is severely reduced due to water stress by affecting photosynthesis including photosystem II (PSII) activity and electron transport. This study emphasised on comparative and priority targeted changes in PSII activity due to progressive drought in seven populations of Panicum antidotale (P. antidotale) collected from Cholistan Desert and non-Cholistan regions. Tillers of equal growth of seven populations of P. antidotale grown in plastic pots filled with soil were subjected progressive drought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…39 The optimal method for evaluating PSII efficacy involves measurements of PSII activity through OJIP analysis or induction curve analysis of plants grown under controlled and stressed conditions 40 and typically exhibits a strong correlation with plant biomass. 41 In contrast, CaO NPstreated plants grown under drought stress exhibited a substantial increase in Φ Pav (Fig. 2F), which is analogous to previous studies in which it was demonstrated that a 50 mg L −1 GO application increased the quantum yield of PSII (F v / F m ) and the actual efficiency of PSII in droughted Aloe vera plants.…”
Section: Cao Nps Improve Plant Growth and Psii Activity Under Drought...supporting
confidence: 88%
“…39 The optimal method for evaluating PSII efficacy involves measurements of PSII activity through OJIP analysis or induction curve analysis of plants grown under controlled and stressed conditions 40 and typically exhibits a strong correlation with plant biomass. 41 In contrast, CaO NPstreated plants grown under drought stress exhibited a substantial increase in Φ Pav (Fig. 2F), which is analogous to previous studies in which it was demonstrated that a 50 mg L −1 GO application increased the quantum yield of PSII (F v / F m ) and the actual efficiency of PSII in droughted Aloe vera plants.…”
Section: Cao Nps Improve Plant Growth and Psii Activity Under Drought...supporting
confidence: 88%
“…Drought is widely recognized as a prominent environmental factor that significantly affects agricultural productivity on a global scale. 3 Plant movement and absorption of nutrients may be limited under conditions of low water content, which can have a subsequent impact on several metabolic processes, such as hormone regulation and chlorophyll production, as well as the timing of phenological events and nutrient acquisition. 4 Unexpectedly, plants already have low use efficiencies for macronutrients (<50%) when the soil is usually wet 5 which is worsened by drought, lowering fertilizer efficacy even further.…”
Section: Introductionmentioning
confidence: 99%
“…Semiquantitative analysis of OJIP curves were performed in MS Excel. In addition, JIP-test parameters were extracted from raw curves following (Strasser et al, 2000;Javed et al, 2021b). The data for JIP-test was subjected to two-way analysis of variance (ANOVA).…”
Section: Discussionmentioning
confidence: 99%